2010
DOI: 10.1016/j.ntt.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposures to low-level chlorpyrifos results in impairments in sustained attention and increased impulsivity in rats

Abstract: Organophosphates such as chlorpyrifos (CPF) are among the most commonly used pesticides in the world. Therefore, it is not surprising that measurable levels of organophosphates (including CPF) are found in over 50% of fresh fruits, vegetables and grains that we consume and that approximately 80% of adults in the US have detectable levels of CPF metabolites in their urine. It is well known that acute exposure to organophosphates can cause cognitive deficits; however, the effects of daily or intermittent contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 28 publications
6
48
0
1
Order By: Relevance
“…The doses evaluated in this study were identified in previous studies (Terry et al, 2003(Terry et al, , 2011Middlemore-Risher et al, 2010) and operationally defined as doses not associated with acute signs of cholinergic toxicity (e.g., fasciculations, seizures, diarrhea, excessive urination, salivation, etc., see reviews, Rusyniak and Nanagas, 2004;Sungurtekin et al, 2006).…”
Section: Chlorpyrifosmentioning
confidence: 99%
“…The doses evaluated in this study were identified in previous studies (Terry et al, 2003(Terry et al, , 2011Middlemore-Risher et al, 2010) and operationally defined as doses not associated with acute signs of cholinergic toxicity (e.g., fasciculations, seizures, diarrhea, excessive urination, salivation, etc., see reviews, Rusyniak and Nanagas, 2004;Sungurtekin et al, 2006).…”
Section: Chlorpyrifosmentioning
confidence: 99%
“…Many studies indicate that repeated exposures to relatively low level of organophosphate pesticides such as chlorpyrifos, and monocrotophos lead to protected impairments of sustained attention and an increase in impulsive behaviors in rats [22,23] .…”
Section: Sub-acute Toxicitymentioning
confidence: 99%
“…When adult rats were treated orally with 18 mg/kg/day chlorpyrifos for 14 consecutive days or every other day for 30 days, they performed more poorly than controls on a test of sustained attention, the 5-Choice Serial Reaction Time Task (214).…”
Section: Experimental Studiesmentioning
confidence: 99%